2022
DOI: 10.1007/s00394-022-02941-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary inflammatory index score and muscle mass and strength in older adults: a study from National Health and Nutrition Examination Survey (NHANES) 1999–2002

Abstract: Purpose Chronic low-grade systemic inflammation affects muscle protein metabolism. The dietary inflammatory index (DII®) is a tool designed to assess the inflammatory potential of the diet. The available data on the association between DII and sarcopenia are limited. We aimed to investigate the association of the DII with components of sarcopenia in individuals over 50 years of age. Methods This cross-sectional study used the National Health and Nutrition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Most of the patients with sarcopenia we included were in the stage of sarcopenia, so muscle mass reduction is significant, and the decrease in muscle strength and physical performance cannot be significant. Furthermore, some studies also showed that the DII was associated with muscle mass [ 20 , 25 ] but not with muscle strength or physical performance [ 11 , 22 , 53 ]. The results of this study are in accordance with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the patients with sarcopenia we included were in the stage of sarcopenia, so muscle mass reduction is significant, and the decrease in muscle strength and physical performance cannot be significant. Furthermore, some studies also showed that the DII was associated with muscle mass [ 20 , 25 ] but not with muscle strength or physical performance [ 11 , 22 , 53 ]. The results of this study are in accordance with our findings.…”
Section: Discussionmentioning
confidence: 99%
“… Forest plot of the risk of sarcopenia in subjects with a high DII vs. a low DII [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. …”
Section: Figurementioning
confidence: 99%
“…In addition, other studies have used the Dietary Inflammatory Index (DII Ⓡ ) to examine the association between diet and systemic inflammation, inflammatory biomarkers (e.g., CRP) ( 45 , 46 ), or chronic conditions. Higher scores of DII, indicating a more pro-inflammatory diet, have been associated with detrimental conditions related to pro-inflammatory state in the body, such as increased inflammatory biomarkers ( 47 ), risks of all-cause and CVD mortality ( 48 ), lower muscle mass and strength ( 49 ) and increased adiposity ( 50 ). The DII scores are based on 45 dietary components that include foods and nutrients which were associated with modulation of six inflammatory biomarkers (IL-1β, IL-4, IL-6, IL-10, TNF-α and CRP) ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…For some reasons, not all of the participants measured 6 times and if one had 4 or more measurements, one peak force from trials 4-6 will be selected while highest peak force from the trials will be selected if anyone complete fewer than 4 measurements(11). Any one who had a history of myocardial infarction within the past 6 weeks, chest or abdominal surgery within the past 3 weeks, knee surgery or knee replacement surgery, severe back pain, a history of brain aneurysm or stroke can't conduct the muscle strength measurements (12).…”
Section: Strength and Speed Measuresmentioning
confidence: 99%